FLEKSIBILITAS JAMINAN PEMBIAYAAN USAHA MIKRO PADA BMT AL-HIKMAH SEMESTA JAWA TIMUR - Ferdinand, Niki Rio; Khusnudin, Khusnudin (I-Economics, 2023)
The existence of MSMEs plays a crucial role as the core of the economic growth in developing countries like Indonesia. They require ease of access to additional capital to expand their businesses. BMT Al-Hikmah Semesta Jawa Timur is one of the Islamic microfinance institutions (LKMS) that provides access to capital for micro-business operators through the flexibility of collateral in their financing products. That case is an intriguing phenomenon worth studying. The research includes examination of the forms of collateral flexibility, the risks associated with implementing this flexibility, and the goals behind its application. This study employs a qualitative approach with data collection techniques such as observation, interviews, and documentation. Based on the research findings, there are various forms of collateral flexibility, including unsecured financing, the use of non-personal collateral, flexible collateral constraints, and a quick collateral release period. However, these flexible collateral arrangements carry the risk of financing repayment failure or default. Service excellence is the ultimate objective of implementing collateral flexibility for members. This research is valuable for those who wish to delve into collateral flexibility in financing.